Semiotika dalam Studi Naskah Tafsir: Analisis Tafsir Q.S Al-‘Asr oleh Binti Al-Syati’ Perspektif Roland Barthes - Asyqar, Naufal; Misnawati, Misnawati (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2025)
This study aims to analyze the application of semiotics in interpreting the Qur'an, specifically in Binti Al-Syati's interpretation of Q.S. Al-'Asr from Roland Barthes' perspective. The scope includes semiotics as a textual analysis method and its role in understanding denotative and connotative meanings of Qur'anic verses. The research focuses on how Binti Al-Syati' implicitly employs semiotics to interpret the word 'aṣr (time) by linking it to life's pressures and trials. The method used is library research with a descriptive-analytical approach. Data is collected from Binti Al-Syati's Tafsir al-Bayan li al-Qur'an al-Karim and semiotic literature by Barthes, Saussure, and Peirce. Analysis identifies linguistic signs (signifier and signified) and unpacks denotative and connotative meanings in Binti Al-Syati's interpretation. The results reveal that Binti Al-Syati' applies Barthes' semiotic principles by interpreting 'aṣr not only as "time" (denotation) but also as "pressure" or life's trials (connotation), evidenced by her cross-referencing of 'aṣr in other verses like Q.S. Yusuf and Q.S. Al-Naba'. The study concludes that semiotics enriches Qur'anic exegesis, offering dynamic and contextually relevant interpretations for modern times.